Geografi dialek bahasa Lampung di wilayah Sumatera bahagian Selatan (Jurnal Bahasa, 2022)
The geographical research on Lampung Language dialects aim to describe the shape of Lampung Language phonology, morphology and lexicon based on geographical research on dialects under quantitative and qualitative through comparison with the Minangkabau, Semende, and Ogan languages, to determine Lampung Language dialects or sub dialects by employing quantitative and qualitative methods, and to determine areas of distribution of relic and innovative elements through mapping Lampung Language diachronically. In order to achieve the aims, participatory field observation method was used which included three stages of resolution, i.e. stage one of data provision conducted through direct interview and participatory observation followed by recording and taking notes on the linguistic unit uttered by informants. Stage two of data analysis by using comparative method; and the stage of presentation of result of analysis which were undertaken by presenting (a) result of research described in the forms of words or sentences and (b) (sub)dialects results transformed into symbols in the mapping.